Expression of the image of a person in the battle genre and its educational value - Assistant D.U. Norqulova (Peerian Journals Publishing, 2022)
The article discusses the significance of the battle genre and the portrait genre, one of the main genres of fine art. Information about the harmony and educational significance of these two genres, its past, future and features, as well as the role and opportunities for educating young people in the system of continuous education, shaping their worldview, all their spiritual qualities.
Keywords: Real; historical genre; thinking; imagination